1991
DOI: 10.1111/j.1600-0773.1991.tb01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Effects in Rats of Toluene (Inhalation) Exposure for Six Months

Abstract: The irreversible CNS effects of six months' exposure to toluene (0, 500, and 1500 p.p.m.) in rats was studied applying a multi-disciplinary approach. After an exposure-free period, neurobehavioural, morphometric, pathological, and biochemical examinations were performed. No neurobehavioural or gross pathological changes were found. Morphometric measurements did not show loss of neurones. At 500 p.p.m. the mean nuclear volume and mean perikaryonal volume and the variation of the values of these parameters was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 35 publications
4
17
0
3
Order By: Relevance
“…After exposure to 1500 ml/m 3 for 6 months the same result was reported (Ladefoged et al 1991). On the other hand, spatial learning and memory were impaired by exposure to 80 ml/m 3 toluene, 6 hours daily for 4 weeks (von Euler et al 1993).…”
Section: Subchronic and Chronic Inhalation Toxicitysupporting
confidence: 70%
“…After exposure to 1500 ml/m 3 for 6 months the same result was reported (Ladefoged et al 1991). On the other hand, spatial learning and memory were impaired by exposure to 80 ml/m 3 toluene, 6 hours daily for 4 weeks (von Euler et al 1993).…”
Section: Subchronic and Chronic Inhalation Toxicitysupporting
confidence: 70%
“…On the day after the last exposure the animals were killed by decapitation in C0 2 anaesthesia. Brains were dissected into hemisphere and hippocampus [14,32,33]. A part of the liver and the whole left kidney were excised.…”
Section: Chemicalsmentioning
confidence: 99%
“…Also, a reduced yield of synaptosomal protein/ g brain weight has been found [13], which may reflect reduced synapse density. However, it has not been possible to demonstrate clear-cut irreversible neurobehavioural and neuropathological effects following long-term exposure to aromatic white spirit [12] or toluene [14]. Cognitive deficits, which are characteristic symptoms in solvent-induced encephalopathy in painters, were not induced in the experimental animals.…”
mentioning
confidence: 99%
“…Animal studies have suggested that extended toluene exposure may induce long-lasting morphological changes in the frontal cortex [2] and hippocampal and cerebellar regions (3). Studies on specific biochemical changes effected by toluene have reported neuronal membrane alterations involving enhanced Ca2+ /Mt+ ·ATPase activity (4], increased intracellular Ca+ [5] and membrane fluidity (6], and alterations in receptor binding and neurotransmitter content [2].…”
mentioning
confidence: 99%